The Influence of the CIRC Learning Model (Cooperative, Integrated, Reading, and Composition) on the Reading Skills Students at Islamic Elementary School - Nurainun, Nurainun; Nasution, Sahkholid (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research describes the influence of the CIRC (Cooperative, Integrated, Reading, and Composition) learning model on reading comprehension skills. This research was carried out at MIN 4 Medan City, which was carried out in the even semester of 2023/2024. This research uses a quantitative approach with a Quasi-Experimental type. This study's population was all class IV MIN 4 Medan City students, totaling 120 students, using proactive random sampling. The research sample consisted of 41 students from classes IV-A and IV-B. The data collection techniques are observation, interviews, documentation, and tests. The data analysis techniques used are descriptive analysis and inferential analysis, namely through normality, homogeneity, and independent t-tests, to test hypotheses with the help of the SPSS 27.0 application. The research results showed a difference in the average score obtained in the control class from 51.05 to 64.47 and in the experimental class from 45.00 to 84.09. This shows that using the CIRC (Cooperative, Integrated, Reading, and Composition) learning model influences students' reading comprehension skills. This is proven by the results of the T-test calculation, which shows a Sig (2-tailed) value of 0.000<0.05 so that H_o is rejected and H_a is accepted, meaning that there is a significant influence between the control and experimental classes.